A highly sensitive and rapid spectrophotometric method for the determination of molybdenum at nano-trace levels in some real, environmental, biological, food and soil samples using salicylaldehyde-benzoylhydrazone - Ahmed, Mohammed Jamaluddin; Afrin, Ayesha; Uddin, Mohammad Ohi (European Journal of Chemistry, 2020)
A very simple, sensitive and highly selective non-extractive new spectrophotometric method has been developed for the determination of molybdenum at nano-trace levels using salicylaldehyde-benzoylhydrazone (Sal-BH). The method is based on the reaction of non-absorbent Sal-BH in a slightly acidic solution (0.0025-0.0075 M H2S04) with molybdenum (VI) to give a light yellowish chelate, which has an absorption maximum at 440 nm. The reaction is instantaneous and absorbance remains stable for over 24 h. The average molar absorption coefficient and Sandell’s sensitivity were found to be 4.32×105 L/mol.cm and 5 ng/cm2 of molybdenum, respectively. Linear calibration graphs were obtained for 0.01-60.00 mg/L of molybdenum having detection limit of 1 µg/L and RSD 0.0-2.0 %. The stoichiometric composition of the chelate is 1:1 (Mo:Sal-BH). A large excess of over 60 cations, anions and some common complexing agents (such as chloride, azide, tartrate, EDTA, SCN- etc.) do not interfere in the determination. The method was successfully used in the determination of molybdenum in several Certified Reference Materials (Alloys, steels, water, hair and bovine liver) as well as in some environmental waters (Potable and polluted), biological samples (Human blood, urine, nails, hair, food and vegetables), soil samples, and solutions containing both molybdenum(VI) and molybdenum(V) as well as complex synthetic mixtures. The results of the proposed method for assessing biological, food and vegetables samples were found to be in excellent agreement with those obtained by ICP-OES and AAS. The method has high precision and accuracy (s = ±0.01 for 0.5 mg/L).